Evaluating the implementation of a hypertension program based on mHealth and community pharmacies integration to primary care centers at a municipality level in Argentina during the COVID-19 pandemic - Esandi, Maria Eugenia (2024)
While pharmacists-led interventions in hypertension have proven effective in high-income countries, their implementation and impact in low- and middle-income countries (LMIC) remain limited. This study assessed the implementation and outcomes of the hypertension program FarmaTeCuida (FTC), which integrated community pharmacies into the public primary care level using information and communication technologies. The study took place during the pandemic in General Pueyrredón, Buenos Aires, Argentina, so modifications to the implementation strategy and expected outcomes were also analyzed